"Eddie would(n't) go!" perceptual-cognitive expertise in surfing. (January 2016) - Furley, Philip; Dörr, Jannik
Abstract: Objectives: The goal of the present research was to investigate the decision making skills of surfers as a function of surfing experience. Design: We used a between-subject quasi-experimental design. Method: Participants ( N  = 76) with different levels of surfing expertise were asked to indicate via a button press which waves they would try to catch in a computer-based video decision-making task that presented videos of approaching waves. Results: The quality of participants' decisions corresponded in a linear manner with the amount of surfing experience, i.e. the more experience a surfer had, the better they were able to decide which waves were surfable and which waves were not. Specifically, more experienced surfers were superior at deciding which waves not to surf. Conclusions: We provided first evidence that highly experienced surfers possess a cognitive advantage compared to less experienced surfers or a non-surfing control group by being better able to distinguish between surfable and non surfable waves. The results are discussed within the expert performance approach as being supportive of the notion that surfing experience led to perceptual-cognitive adaptations that allow surfers to pick the right waves. Highlights: Perceptual-cognitive skills are important in sport expertise. We examined decisions making skills in wave surfing. Expert surfers were superior (vs. novices and controls) at deciding on which waves to surf.